Woyzeck on the highveld - Hutvágner, Éva (Studia Mundi – Economica, 2015)
This paper examines the performance, Woyzeck on the Highveld by The Handspring Puppet Company from an intercultural point of view. The different attitudes concerning its reception (with a strong emphasis made on the 2011 performance in Hungary) are comparable with the historicity of the classical text of the drama.